Sistem Pakar Diagnosa Penyakit Pada Kelinci Anggora Menggunakan Metode Certainty Factor - Sari, Lidiya Okta; Elfianty, Lena; Alinse, Rizka Tri (MEANS (Media Informasi Analisa dan Sistem), 2022)
Health is not only important for humans, but also for flora and fauna. Especially for animals that are often kept by humans either just for hobbies or for breeding. One of the animals that is often kept by humans is the Angora rabbit. Angora rabbits can be used as pets to be collected or farmed for resale. Angora rabbits are often attacked by diseases due to various factors, both because of the condition of the cage and the food. One that causes farmers to lose money is due to disease. The number of rabbit deaths caused by disease is quite high, ranging from 15% to 40%. Death occurs from birth to weaning. Some of the factors that cause disease are carelessness in maintaining cage sanitation, poor quality feed, insufficient feed volume, dirty or insufficient drinking water, lack of nutrients, contracting other sick rabbits, weather changes, and ignorance about Angora rabbit disease. Based on test data using the blackbox testing method, this expert system website is running well. Conclusion Expert System for Diagnosing Diseases in Angora Rabbits Using the Certainty Factor Method is a program that can diagnose disease in Angora rabbits and produce a percentage level of probability that Angora rabbits have the disease, based on the condition of the symptoms of the Angora rabbit that the user chooses.